2017
DOI: 10.1371/journal.pone.0188564
|View full text |Cite|
|
Sign up to set email alerts
|

Widespread local chronic stressors in Caribbean coastal habitats

Abstract: Coastal ecosystems and the livelihoods they support are threatened by stressors acting at global and local scales. Here we used the data produced by the Caribbean Coastal Marine Productivity program (CARICOMP), the longest, largest monitoring program in the wider Caribbean, to evidence local-scale (decreases in water quality) and global-scale (increases in temperature) stressors across the basin. Trend analyses showed that visibility decreased at 42% of the stations, indicating that local-scale chronic stresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
(74 reference statements)
0
12
0
Order By: Relevance
“…A chronic decline in light attenuation (a proxy for deteriorating water quality) over the monitoring period of CARICOMP sites (1992-2015) was found to be widespread across the Caribbean, despite being caused by local level anthropogenic activities such as increased infrastructural development and other changes in land use. For example, decadal declines in water clarity were reported by 42% of CARICOMP sites (Chollett et al, 2017). They also reported that decadal increases in the water temperature of FIGURE 5 | Seasonal pattern of mangrove productivity in the Caribbean as indicated by litter fall and shown separately for the common species.…”
Section: Physical Environmentmentioning
confidence: 98%
See 4 more Smart Citations
“…A chronic decline in light attenuation (a proxy for deteriorating water quality) over the monitoring period of CARICOMP sites (1992-2015) was found to be widespread across the Caribbean, despite being caused by local level anthropogenic activities such as increased infrastructural development and other changes in land use. For example, decadal declines in water clarity were reported by 42% of CARICOMP sites (Chollett et al, 2017). They also reported that decadal increases in the water temperature of FIGURE 5 | Seasonal pattern of mangrove productivity in the Caribbean as indicated by litter fall and shown separately for the common species.…”
Section: Physical Environmentmentioning
confidence: 98%
“…Physical environmental data were collected for at least 3 years and up to 22 years at 29 sites in coastal ecosystems (coral reefs, seagrasses, mangroves) in 13 countries across the Caribbean, beginning in 1992 (CARICOMP, 1997b;Chollett et al, 2017).…”
Section: Physical Environmentmentioning
confidence: 99%
See 3 more Smart Citations